Bank-based versus market-based financing: Implications for systemic risk - Bats, Joost V.; Houben, Aerdt C.F.J. (Journal of Banking & Finance, 2020)
Against the background of the great financial crisis, this paper assesses the merits of bank-based versus market-based financing by exploring the relationship between financial structure and systemic risk. The findings indicate that bank-based financial structures are associated with higher systemic risk than market-based financial structures. In relatively bank-based financial structures, bank financing is found to increase systemic risk while market financing decreases systemic risk. By contrast, in relatively market-based financial structures, bank and market financing do not impact systemic risk. Together, the results signal that market-based financial structures are more resilient to systemic risk.